Pengaruh Konsep Diri dan Kecerdasan Emosional terhadap Kemampuan Pengambilan Keputusan Siswa - Rina Nur Hidayati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
This study aims to investigate the effect of self-concept and emotional intelligence on students' decision making abilities. This research was conducted in eighth grade students of junior high schools in the city of Depok. Determination of the sample is done using cluster random sampling obtained by the sample size of 40 students. The method used to investigate the magnitude of the effect is to use multiple linear regression. Based on the results of research that has been done obtained information that there is a significant influence between self-concept and emotional intelligence on the decision-making abilities of students. The influence of self-concept and emotional intelligence separately on the ability of decision making were 21.72% and 28.09%, respectively. While the influence of the two independent variables together is equal to 81.7%. This illustrates that self-concept and emotional intelligence are important components that must be considered by educators in particular, in developing decision-making abilities.